Constitution Identification System for Traditional Chinese Medicine (TCM) Based on Correlation Between TCM Constitution and Physical Examination Indices - Yue Luo; Bing Lin; Chuan-Biao Wen; Jie-Lin He (KeAi Communications Co., Ltd., 2018)
ABSTRACT: Objective Identification of one's constitution based on a combination of features and back propagation neural network theory is needed in modern medicine and traditional Chinese medicine (TCM). We describe a method to identify one's constitution based on TCM constitution classification and a physical index model.Methods We created a constitution identification system based on neural network using Visio Studio development tool. We report the initial implementation of the system, the accuracy of which was verified using actual data.Results We found a relatively strong correlation between TCM constitution and physical indicators.Conclusion Finally, our report describes a possible application of the proposed system. Keywords: Constitution identification system, Neural network, Physical examination indices, Correlation model